The Romans in the lower Dniester region and Boudjak - Jarzęcki, Krzysztof (Acta Archaeologica Lodziensia, 2021)
In the early years AD the city of Tyras remained in an alliance with the Thracian kings. After 46 AD, and possibly slightly earlier, the city entered into an alliance with the Sarmatian rulers of Olbia, who are allies of Rome. In 56/57 AD Tyras could receive a guarantee of freedom from Rome. At the time of the Flavians Tyras began to strike coins typical for the eastern provinces of the Roman Empire. This could have been the result of a “monetary union”. It is possible that during this same period the city received a customs privilege. After the Dacian wars of Trajan a Roman garrison was established in Tyras. In the 2nd century, most probably during Hadrian’s reign, the city was incorporated into Lower Moesia. Around the middle of the third century, due to the difficult military situation on the Danube, the permanent garrison was withdrawn from Tyras. In the second half of the third century with the permanent presence of the Romans is confirmed only in the southern part of Boudjak, on the Danube. At the same time in those areas trade with the inhabitants of Boudjak increased at the cost of the Lower Dniester area. In such circumstances, the city declined economically. The collapse of ancient culture in this area should be connected with the invasion of the Huns in 375-376.